Loading of cell cultures with cholesterol‐dextran particles as a new functional test for Niemann–Pick type C disease. Issue 3 (6th February 2022) - Majer, Filip; Asfaw, Befekadu; Kuchař, Ladislav; Mušálková, Dita; Steiner‐Mrázová, Lenka; Dobrovolný, Robert; Ledvinová, Jana; Hřebíček, Martin
Abstract: Deuterium‐labeled cholesterol‐dextran particles (d4‐CholDex), prepared by co‐precipitation, were internalized by cultured human skin fibroblasts and HEK293 cells. Subcellular particles from d4‐CholDex‐treated HEK293 cells were fractionated on iodixanol gradients. More than 60% of d4‐cholesterol (d4‐UC) in the gradient co‐fractionated with lysosomal markers and NPC1. This and formation of d4‐cholesteryl esters (d4‐CE) in the cells suggests that d4‐CholDex is lysosomally processed. In accordance with these findings, we observed an increase in lysosomal cholesterol content by fluorescence microscopy in CholDex‐loaded cells. Fibroblast cultures including 13 NPC1‐deficient, four heterozygous and six control lines were treated with d4‐CholDex at final d4‐UC concentration of 0.05 mg/ml (127.98 μmol/L) for 3 h and chased for 48 h in medium without d4‐CholDex. Concentrations of d4‐UC and d4‐CE in harvested cells were measured by tandem mass spectrometry (MS/MS). d4‐UC/d4‐CE ratios were elevated in NP‐C lines compared to controls ( n  = 6, mean = 4.36, range = 1.89–8.91), with the highest ratios in severe NP‐C1 phenotypes and the lowest in adolescent/adult type patients. There were overlaps between NP‐C1 forms: early infantile ( n  = 1, mean = 48.6), late infantile ( n  = 4, mean = 36.3, range = 20.6–54.0), juvenile ( n  = 5, mean = 24.7, range = 13.4–38.3), adolescent/adult ( n  = 3, mean = 14.5, range = 11.7–19.8). The ratios in NP‐C1 heterozygotes were mildly elevated ( n  = 4, mean = 16.4, range = 14.9–17.4) and comparable to patients with adolescent/adult NP‐C1. The test can be useful in evaluation of suspected NP‐C patients with inconclusive results of biomarker or molecular tests. Its advantages include standardized preparation of particles with longer shelf life at 4 °C, quantitative results, and no requirement for radioactive chemicals.